A Game-Based Shooting Practice Model to Improve the Basketball Shooting Accuracy among High School Students - Andi Hasriadi Hasyim; Iyan Nurdiyan Haris; Muh. Ali Akbar (MASI Mandiri Edukasi, 2026)
This study aimed to determine the effect of a game-based shooting learning model on improving basketball shooting accuracy among high school students. The method used was a quasi-experimental study with a pretest-posttest control group design. The study sample consisted of 60 students divided into two groups: an experimental group (game-based model) and a control group (conventional drill method), each with 30 students. The research instrument was a basketball shooting test to measure shooting accuracy. Data analysis used descriptive statistics and an independent sample t-test. The results showed that both groups improved, but the experimental group showed greater improvement, with an average posttest score of 83.40 compared to 70.80 in the control group. The statistical test results showed a significant difference (p < 0.05), indicating that the game-based learning model was more effective in improving shooting skills. Theoretically, the game-based learning model is grounded in the constructivist approach and Teaching Games for Understanding (TGfU), which emphasize active student involvement, decision-making, and learning within a real-world game context. This approach not only improves technical skills but also students' motivation and tactical understanding. Therefore, the implementation of student-centered, game-based learning is highly recommended in physical education.